Inventário da flora hepática (Hepaticae) de áreas de várzea e Terra Firme da Estação Científica Ferreira Penna, Floresta Nacional de Caxiuanã, Pa - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2003)
The inventory conducted in the Scientific Station Ferreira Penna found a high floristic diversity of trees in the area, raising the hypothesis that it would also be found a great floristic diversity of other groups, such as bryophytes, fungi and lichens. Preliminary data shows the presence of 123 species of bryophytes (mosses and liverworts), 63 taxa of fungi and 134 species of lichens. This work aims to continue the inventory of the hepatic flora of the ECFPn, carrying out taxonomic and ecological studies of the species. The methodology used consisted of collecting liverworts, noting data related to the ecosystem and substrate in which they were found. In this work, only samples collected from dryland forests and floodplains were analyzed. For identification, specialized bibliography was used and/or comparison with material identified by specialists. We identified 53 species, distributed in 27 genera and 6 liverworts families. The family Lejeuneaceae has stood out for presenting the greatest diversity of species and number of occurrences. The genera: Lejeunea, Ceratolejeunea and Piagiocbila, are represented by 6, 5 and 5 species, respectively. Ceratolejeunea comuta (Lindenberg) Schiffner, Cololejeunea oblíqua (Nees & Montagne) S.Arnell and Tracbylejeunea aneogyna (Spruce) Grolle are the most frequent species. The genus Vitalianthus is mentioned for the first time for the state of Pará with the identification of the species V. urubuensis Zartman & Ackerman. The occurrence of species not previously mentioned, confirm the hypothesis that the specific diversity of this group would grow with the increase of the studied area.
Inventory of the liverwort flora (Hepaticae) of floodplain and terra firme areas of the Ferreira Penna Scientific Station, Caxiuanã National Forest, Pa
Keywords: Hepaticae; Briófítas; Fungos; Líquens; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL